2022
DOI: 10.3389/fnagi.2021.732840
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms Mediated the Relationship Between Odor Identification and Cognition in Alzheimer's Disease Spectrum: A Structural Equation Model Analysis

Abstract: Background: Odor identification dysfunction is an early predictor of the development of Alzheimer's disease (AD), but neuropsychiatric symptoms (NPS), which are common in AD and mild cognitive impairment (MCI), are also associated with odor identification dysfunction. Whether NPS affect the specificity of using odor identification dysfunction to predict cognitive decline in AD and MCI remains unclear.Methods: Patients (233 with MCI and 45 with AD) and 45 healthy controls (HCs) underwent assessments of odor ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…In recent years, some scholars have analyzed the allocation and management of public sport facilities resources, combined with the characteristics of public sport facilities resources, mined the data characteristics of customers by Python and the spatial spectrum estimation method, and put forward the optimization algorithm for the allocation and management of public sport facilities resources [ 5 ]. Scholars also use the clustering method to estimate the spatial distribution and management of public facilities and reduce the dispersion of sport resources [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some scholars have analyzed the allocation and management of public sport facilities resources, combined with the characteristics of public sport facilities resources, mined the data characteristics of customers by Python and the spatial spectrum estimation method, and put forward the optimization algorithm for the allocation and management of public sport facilities resources [ 5 ]. Scholars also use the clustering method to estimate the spatial distribution and management of public facilities and reduce the dispersion of sport resources [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that affective symptoms and psychosis symptoms are associated with olfactory dysfunction in patients with AD [ 36 ], major depressive disorder [ 7 ], schizophrenia [ 12 ], and bipolar disorder [ 9 ]. There was no correlation between olfactory function and neuropsychiatric symptoms in patients with GPI.…”
Section: Discussionmentioning
confidence: 99%
“…AD prodromal symptoms are loss of short-term memory with conservation of long-term memory. Progressive deterioration of executive function and motivation disorders are also developed (Wang et al 2022 ). A range of neuropsychiatric disorders, including agitation, olfactory dysfunction, dyspraxia, sleep disorders, and motor dysfunctions are developed during AD neuropathology (Yu et al 2021 ; Zhang et al 2022 ).…”
Section: Overview Of Alzheimer’s Diseasementioning
confidence: 99%